Studying the electron flow formation in magnetron guns with a secondary emission metallic cathode - Dovbnya, A.N.; Reshetn’yak, N.G.; Zakutin, V.V. (Вопросы атомной науки и техники, 2001)
Presented are the results of studies concerning the multybeams systems and considering the possibility to increase the output current amplitudes by changing the geometrical dimensions of guns.